ITC study on the interaction of some bile salts with tragacanth, Arabic, and guar gums with potential cholesterol-lowering ability - Massa, Michele; Compari, Carlotta; Fisicaro, Emilia (Frontiers in Nutrition, 2023)
Introduction The urge of designing new safe and natural functional foods to control blood lipids and dispensable without the need of physician supervision, has increased especially after the coming into effect of the recent EU Commission regulation 2022/860, that regulates the consumption of “red yeast rice,” made by fermentation of rice with Monascus purpureus, and perceived as a natural functional food, due to a health risk for frail consumers. The results of the present work are a part of the systematic study we are carrying out of the binding ability of some soluble dietary fibers (SDF) from different natural sources toward selected bile salts (BS). Methods Measurements were carried out by isothermal titration calorimetry (ITC) with the idea to shed light on the mechanism, if any, by which they show cholesterol-lowering activity. Results and discussion Epidemiological studies are sometimes conflicting and offer only hypothesis about the mechanism of action, the most accredited being the reduction of reabsorption of BS in the gut. Previous measurements done on negatively charged pectin and alginate, showed specific binding interaction with monomer NaDC for pectin and no interaction at all for alginate. Chitosan, positively charged and soluble only at low pH, in 100 mM acetate buffer at pH = 3 shows strong exothermic interactions with NaTC and NaTDC. Here we considered two plant exudates (Arabic gum and tragacanth gum) and guar gum, extracted from guar beans, and their interaction with the same bile salts. ITC measurements do not evidence specific interactions between gums and the studied BS, so that their cholesterol lowering ability, if any, is due to a different mechanism very probably bound to the viscosity increase. Moreover, the addition of NaC, the most abundant BS in the bile, at very low concentration (under the cmc) causes a structural change of the solution. The obtained results seem to corroborate the hypothesis that the cholesterol lowering activity is related to the increase in viscosity of guar solution favored by NaC, the major component of the bile.